Fenomena Chatbot AI Sebagai Teman Curhat: Implikasi Pada Hubungan Antarpribadi di Era Digital - Yoseppin, Graciella; Nagita Dewi, Putu Ayu Mas; Purba, Yuni Kasih (School of Communication Science and Media Business, 2025)
The phenomenon of using AI chatbots as confidants has been on the rise alongside advancements in communication technology. This research examines the increasing popularity of AI chatbots as companions for sharing personal thoughts in the digital era. By referencing the Beyond Human Communication theory, that highlights the connection between people and technology in modern communication, we used a qualitative approach and a systematic literature review to explore how chatting with these bots affects personal relationships and how we perceive communication quality. Results reveal that AI chatbots, by Natural Language Processing (NLP) abilities, can create a communication experience that feels quite like talking with another person. Chatbot AI offer emotional support that readily available. However, relying too much on chatbots can hinder a person’s ability to engage in deeper, more meaningful conversations with other humans. While these bots can provide quick and accurate responses, they lack the depth and significance that come with human interactions. This research highlights the need to strike a balance between using technology and maintaining genuine human connections to keep our social relationships strong.